PENGARUH PEMBERIAN MAKANAN TAMBAHAN PADA BALITA KURANG ENERGI PROTEIN (KEP) PENGUNJUNG BALAI PENELITIAN DAN PENGEMBANGAN GANGGUAN AKIBAT KEKURANGAN IODIUM (BPP GAKI) Magelang - Sri Supadmi; Sukati Saidin; Muhamad Samsudin (Persagi, 2008)
The Impact of Supplementary Food On The Child With Protein Energy Malnutrition (PEM) The Visitor of Centre IDD Magelang.Background: Economic crisis result the purchasing power of society become to descend and weak. This matter affect at downhill it health and nutrition status at the under five child. Problem of Insuffiency of Energi Protein Malnutrition (PEM) at the under five child visitor of Center IDD Magelang show the real indication that is in the 2002 found prevalence of PEM was 63.2%. The aim of this study was measured the impact nutrition supplementary with nutritional status the under five child visitor of Center IDD Magelang.Methods: Study design was pre and post test. Research type was applicative research. Subject were 30 child old age 6-59 of month at Centre 100 Magelang. It was conducted by purposive taken with quota sampling. The intervention inform supplementary food made by flour of rice, soybean/tempe, fish/lele, spinach, flour of carrots and sugar. Data analysis were used the t-test.Results: The t-teat are result which significant of at measurement of nutritional status use the weight-for-age (W/A) index (t=3.465; p<0.05) and there are increase of weight after intervension as much 700g. Measurement of nutrition status use the weight-for-high (W/H) index give the impact which significant (t=3.156; p<0.05) and there are increase addition of high as much 1.5 cm. There are decreased of several PEM equal to 6.6% with W/A and 16.7% with W/H index, improvement become the normal status equal to 13.3%.Conclusion: The food supplementary of children under five years old the impact of there are difference of weight in before and after intervention also give impact of nutritional status.Keywords: supplementary food, PEM, children under five years old.